The development of the adolescent mother and her baby 's attachment - Eva Neri Rubim Pedro; Daisy Zanchi de Abreu Botene; Maria da Graça Corso da Motta; Nair Regina Ritter Ribeiro; Ana Amélia Antunes Lima (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
The study concerns about the development of the attachment between the adolescent mother and her baby. Its objectives are to know the adolescent's experience as a mother; to recognize the manifestations of attachment between mother/baby and to know the factors that facilitate and/or interfere the development of the attachment. It is a longitudinal study with a qualitative approach, realized with six adolescent mothers, between thirteen and nineteen years old, and their babies, linked to the Family Health Program (FHP) from Vila Pinto, a popular class comunity in Porto Alegre/RS. The collection of the information was realized through semi-structered interviews and participatory observations. For the analysis of the information, an analysis of the content was used, from where the following cathegories emerged: satisfaction with the maternity; bonding-attachment; familiar support and interrupted project of life. The results indicate that the familiar and the partener's support are the bonding facilitating factors, since youngesters have this support, show an affectionate relationship with their babies, but we can not to say that others adolescents whose don't have this support, don't development of the attachment with your sons.